Az eperjesi evangélikus kollégium tanárainak egyetemjárása a 19. század közepéig - Kónya, Péter (Gerundium, 2017)
University Studies of Professors at the evangelical Colleg of Presov up to 19th century. Evangelical College in Presov, as one of the most important evangelical schools in Hungary, considered the high quality education of its teachers to be very important since its establishment, and as a rule, the positions of professors were occupied by the graduates of German universities. Before establishment of the College, the Town Council likewise had seen to it that the humanistic „gymnasium” had been lead by rectors with high quality university education. This paper aims at creating a portrait of studies of professors at Evangelical College in Presov, and at its predecessor – the Municipal Lutheran Gymnasium over a period of three centuries, from the half of the 16 th to the half of the 19 th centuries whereby the data about its rectors, conrecors and subrectors were used as a source. In the period of these three centuries 111 Presov Evangelical rectors, conrectors and subrectors acquired their education at 26 universities or colleges. Most of them, 34, studied at Wittenberg (30%), followed by Jena (11), Tübingen (7), Thorn (6), Halle (4), Vienna (4) and Frankfurt (4). Three of them graduated from the University in Altdorf, two in Greifswald and the Reformed College in Sarospatak and by one in Rostock, Prague, Gdansk, Graz, Strassburg, Helmstädt, Erfurt, Giessen, Erlangen, Rinteln, Paris, Vratislav, Dresden and Göttingen. Other 16 professors studied at unknown places, eventually did not obtained higher education. 20 professors obtained their education at more than one university or college, most of them (7) in the first period of existence of the College (1667–1711), and least of them (2) in the first half of the 19 th century.